Adsorption of fluoride on a green adsorbent derived from wastepaper: Kinetic, isotherm and characterisation study - Khalid S. Hashim; Abdul Kareem K. Alsaffar; Rasha Salah Alkizwini; Abduljabar H. Ali; Eduardo Alberto López-Maldonado; Jasim M. Salman; SoltanMS. Alenezi; Phil Salmon; Hassimi Abu Hasan; Nadhir Al-Ansari (Case Studies in Chemical and Environmental Engineering, 2023)
The excessive concentration of fluoride (F−) in water represents a grave problem for several countries, especially those that depend on groundwater as a main source of drinking water. Therefore, many treatment methods, such as chemical precipitation and membrane, were practised to remove F− from water. However, the traditional methods suffer from many limitations, such as the high cost and the slowness. Hence, many studies have been directed towards developing novel and effective water defluoridation methods. In this context, the current study investigates the development of an eco-friendly adsorbent by extracting Ca, Al, and Fe from industrial by-products, precipitating them on sand particles, and using this new adsorbent to remove F− from water. The removal experiments were commenced under different pH levels (3-10), contact times (0–240 minutes) and concentrations of F− (7.5–37.5 mg/L). X-ray fluorescence (XRF), X-ray diffraction Investigator (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray Spectroscopy (EDX) methods were used to characterise the green adsorbent. Adsorption isotherm and kinetic studies were also conducted to define the adsorption type. The results confirmed that the new adsorbent could remove as high as 86% of F− at pH, contact time, agitation speed and adsorbent dose of 10, 180 minutes, 200 rpm and 15 mg/L, respectively. The characterisation studies prove the occurrence of the sorption process and the suitability of the morphology of the adsorbent for F− removal. Adsorption kinetics follow better with a pseudo-first-order model that indicates the predominance of physisorption, which agrees with the FTIR results. The isotherm study indicated that Langmuir isotherm is more suitable for representing data with an R2 value of 0.992, which means the adsorption of F− occurs as monolayer adsorption on homogeneous sites on the surface of the new adsorbent. In summary, it can be concluded that the developed adsorbent in this study could be a promising alternative to the traditional F− removal methods.